A survey of gastroenterologists in the United States on the use of central neuromodulators for treating irritable bowel syndrome. Issue 3 (20th June 2021) - Nulsen, Benjamin; LeBrett, Wendi; Drossman, Douglas A.; Chang, Lin
Summary: Background: Central neuromodulators are an effective treatment for irritable bowel syndrome (IBS) but may be used less frequently than other therapies. Aims: To survey gastroenterologists in the United States (US) about their use of neuromodulators in patients with IBS. Methods: A 23‐question survey was distributed to gastroenterologists in the United States. Comparisons in prescribing practices were conducted between (a) gastroenterologists who were "high prescribers" versus "low prescribers" of neuromodulators in patients with IBS and (b) gastroenterologists and "gastroenterology experts" in the use of neuromodulators using descriptive statistics and multivariable logistic regression analyses. Results: The 525 gastroenterologists who were surveyed used neuromodulators for a median range of 21%‐30% of their patients with IBS. Neuromodulators were described as extremely/very important in managing IBS by 55% of clinicians. Significant predictors of high‐prescribing behaviour were academic versus clinical practice setting (odds ratio [OR] 2.60 [95% CI 1.61‐4.20]), disorders of brain‐gut interaction focused practice (OR 4.80 [2.60‐8.84]), and greater perceived effectiveness of neuromodulators (OR 2.75 [1.30‐5.84]). Compared to gastroenterologists, experts prescribed neuromodulators to a higher percentage of their patients with IBS (41%‐50% vs 21%‐30%; P  = 0.019) and more frequently found neuromodulators effective (70% vs 27%; P  = 0.003). However, concern about side effects was the most common barrier to neuromodulator use (59%). Conclusions: The majority of US gastroenterologists believe central neuromodulators are important in treating IBS, and 27% believe they are effective in most patients. High prescribers are in academic practice, focus in IBS and perceive central neuromodulators as effective. Education is needed to improve gastroenterologists' prescribing behaviour. Abstract : A survey of more than 500 gastroenterologists in the United States found that central neuromodulator use in the treatment of irritable bowel syndrome (IBS) varies among providers, with those in academics and IBS‐focused practices more likely to use these medications. These findings highlight the need for education to optimize gastroenterologists' use of central neuromodulators.